Pengaruh Animosity terhadap Boycott Intention Studi Kasus Starbucks Indonesia 2023-2024 - Rimbo, Denise Alexa; Levina, Levina; Soehadi, Agus W; Sumarlin, Antonius W (Universitas Prasetiya Mulya, 2025)
Known for its variety of coffee, tea, and snacks in a comfortable atmosphere, Starbucks has expanded globally, including to Indonesia in 2002. However, in 2023, the company faced market value decline due to issues of supporting Israel, resulting in boycott calls. The aim of this study is to examine and analyze the influence of consumer animosity on the boycott intention of the brand Starbucks Indonesia using cognitive-affective behavioral and animosity theories. The research methodology is quantitative, involving 191 questionnaire respondents, analyzed using SPSS 29 and AMOS 24. Results show that consumer animosity and affective evaluation were found to influence boycott intention. However, cognitive judgment does not have a significant influence. Therefore, it is important for Starbucks brand managers to monitor and proactively respond to sensitive global issues, especially those that may trigger consumer animosity.